The colonial contract and the founding of the Peruvian republic: a decolonial analysis - Riveros-Ramos, Jonathan (2022)
This article focuses on analyzing the relationship between the colonial contract and the founding of the Republic of Peru, centering on key categories such as racism, capitalism, patriarchalism and eurocentrism from the decolonial philosophy. The objective is to demonstrate the relationship that exists between the Colonial Contract and the foundation of the Peruvian Republic to understand the philosophical, political, economic, social and epistemic problems that Peru is going through in the XXI century. The present work is of philosophical and documentary research, with an analectic and genealogical method which will allow us to understand from a geopolitics of knowledge that is not eurocentric, the bifurcations and the configuration has had the social contract theory in the founding of Peru. The importance of the present work will allow us to understand how the relations of domination of the colonial contract operate in Peru in the XXI century.